Mandible and teeth characterization of the Gravettian child from Gargas, France - Mona Le Luyer; Sébastien Villotte; Priscilla Bayle; Sélim Natahi; Adrien Thibeault; Bruno Dutailly; Carole Vercoutère; Catherine Ferrier; Christina San Juan-Foucher; Pascal Foucher (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
While affinities and interactions between archaic and modern human populations (i.e. 200,000-40,000 BP in Eurasia) at macro-evolutionary and continental scales have received considerable attention, there has been less emphasis on the population history of Europe between 40,000 and 26,000 BP (i.e. prior to the Last glacial Maximum, LGM) when only modern humans were present. Here we examine the immature mandible from Gargas (France, ca. 29,000 cal BP), which displays a modern morphology overall with some archaic features rarely seen, if at all, in European Pleistocene and Holocene modern humans. In particular, the Gargas child has a very broad mandible, large tooth crowns with extreme deciduous and permanent mesiodistal molar diameters and a deciduous first molar with a quantity of enamel never previously reported. Furthermore, this child exhibits a supernumerary permanent tooth in the incisor region, a rare congenital disorder so far described for only five other pre-LGM modern humans. Finally, our results also highlight previously undocumented spatial differences in the tooth crown dimensions of Upper Palaeolithic fossils.